Beyond Ketamine and Phencyclidine: Analytically Confirmed Use of Multiple Novel Arylcyclohexylamines. Issue 4 (8th August 2017) - Thornton, Stephen; Lisbon, David; Lin, Thomas; Gerona, Roy
ABSTRACT: Background : Methoxetamine and 3-methoxy-phencyclidine are novel arylcyclohexylamines whose use and clinical toxicity are poorly reported in the medical literature. We report a case of analytically confirmed use of both methoxetamine and 3-methoxy-phencyclidine. Case Report : A 27-year-old male presented 10 hours after insufflating an Internet-obtained powder. He was hypertensive, tachycardic, and demonstrated dissociated affect, a delayed verbal response to questions, ataxia, and vertical nystagmus. A urine drug screen was positive for phencyclidine and 11-nor-delta9-THC-9-carboxylic acid. He was admitted and his mental status and blood pressure normalized eight hours later. Blood samples (0, 2, and 3 hours from arrival) and the powders were analyzed by liquid chromatography-quadrupole time-of-flight mass spectrometry. Methoxetamine and 3-methoxy-phencyclidine were detected in all samples (279 ng/ml, 205 ng/ml, and 180 ng/ml for methoxetamine; 167 ng/mL, 131 ng/mL, and 90 ng/ml for 3-methoxy-phencyclidine at 0, 2, and 3 hours, respectively). No phencyclidine or tetrahydrocannabinol was detected. Two powders contained methoxetamine while one contained 3-methoxy-phencyclidine. Conclusion : The literature regarding methoxetamine and 3-methoxy-phencyclidine toxicity is limited. Methoxetamine use is associated with altered mental status, ataxia, and hypertension. Toxicity from 3-methoxy-phencyclidine is poorly described. There is no prior case describing serial qualitative analysis. Health care providers should be aware of the novel arylcyclohexylamines and their toxicity.